Towards the unified non-classical physics: account for quantum fluctuations in equilibrium thermodynamics via the effective temperature - Rudoy, Yu.G.; Sukhanov, A.D. (Condensed Matter Physics, 2005)
The concept of effective temperature (ET) T*(T₀, T ) is used in order to
approximately “quantize” the thermodynamic functions of the dynamical
object which is in the thermal equilibrium with thermal bath being at constant
temperature T (T₀ = E₀/kB, where E₀ is the ground-state energy,
kB – Boltzmann constant, is the characteristic “quantum” temperature of
the system itself). On these grounds the extensive comparative investigation
is carried out for the “standard model” of statistical mechanics – the
one-dimensional harmonic oscillator (HO). Three well-known approaches
are considered and their thermodynamic consequences thoroughly studied.
These are: the exact quantum, or non-classical Planck-Einstein approach,
intermediate, or semiclassical Bloch-Wigner approach and, finally,
the pure classical, or Maxwell-Boltzmann approach. Концепція ефективної температури (ET) T*(T₀, T) використовується для того, щоб наближено “квантувати” термодинамічні функції
динамічного об’єкту, який є в термічній рівновазі з термостатом при
постійній температурі T (T₀ = E₀/kB, де E₀ – енергія основного
стану, kB – постійна Больцмана, – є характеристичною “квантовою”
температурою самої системи). Базуючись на цьому, здійснено екстенсивне порівняння дослідження “стандартної моделі” статистичної
механіки – одновимірного гармонійного осцилятора (ГО). Розглянуто три добре відомі підходи та добре вивчено їх термодинамічні
наслідки, а саме: точний квантовий або некласичний підхід ПланкаЕйнштейна, проміжний або напівкласичний підхід Блоха-Вігнера і,
нарешті, чисто класичний або підхід Максвелла-Больцмана.